Social dimensions of Weather Index Insurance in reaching marginal stakeholders: Lessons from Asia and Africa. Webinar summary report - Aheeyar, Mohamed M. M.; de Silva, Sanjiv; Barua, A. (International Water Management Institute, 2021)
Climate change will have an impact on natural resources, water being one of them, affecting the availability of water including increasing the intensity of floods and droughts. It is also a known fact that the impact of natural hazards is felt more in developing countries compared to developed countries and especially by vulnerable and marginalised groups within communities. Such groups are more at risk due to their greater exposure (e.g. cultivation on low-lying land) and poor capacity to adapt (e.g. less access to irrigation and financial assets- poor literacy and agency) and hence lower resilience. This is compounded by the fact that financial support from the government is not readily available in many developing countries for all losses.